What are the levels and mechanisms/processes of language evolution? - Gontier, Nathalie (Language sciences (Oxford), 2017)
Modern evolutionary biology is currently characterized by epistemological divergence because, beyond organisms and genes, scholars nowadays investigate a plurality of units of evolution, they recognize multilevel selection, and especially from within the Extended Synthesis, scholars have identified a plurality of evolutionary mechanisms that besides natural selection can explain how the evolution of anatomical form and functional behavior occur. Evolutionary linguists have also implicated a multitude of units, levels and mechanisms involved in (aspects of) language evolution, which has also brought forth epistemological divergence on how language possibly evolved. Here, we examine how a general evolutionary methodology can become abstracted from how biologists study evolution, and how this methodology can become implemented into the field of Evolutionary Linguistics. Applied Evolutionary Epistemology (AEE) involves a systematic search and analysis of the units (that what evolves), levels (loci where evolution takes place), and mechanisms (means whereby evolution occurs) of language evolution, allocating them into ontological hierarchies, and distinguishing them from other kinds of evolution. In this paper in particular, we give an in-depth analysis of how AEE enables an identification, examination, and evaluation of levels and mechanisms of language evolution, and we hone in on how hierarchies and mechanisms of language (evolution) can and have been defined differentially. For an in-depth analysis of units of language evolution, we refer the reader to Gontier (2017) for which this paper functions as a follow-up. Thus, rather than present a specific theory of how language evolved, we present a methodology that enables us to unite existing research programs as well as to develop theories on the subject at hand. •Provides a new methodology to identify levels, and mechanisms or processes of language evolution.•Supplies guidelines for how evolutionary hierarchies and unifying theories of language evolution can be built.